Over-the-Counter Statins: A Gateway to Misuse - Abdelaal, Ahmed; Ng, Kelvin; Ou, Kelsie (The Meducator, 2018)
One in four Canadians over the age of 20 are at a significant risk of developing cardiovascular disease. Despite their proven efficacy as a lipid-loweing therapy for patients at risk, statins continue to be under-prescribed and underused. Proponents of over-the-counter statins argue that increased accessibility will improve usage and lighten the economic burden of cardiovascular diseases. Furthermore, statins have proven to be clinically effective at low doses. Despite these potential benefits, statins should not be approved as over-the-counter drugs as they are accompanied by greater risks of misuse compared to prescription statins. Over-the-counter approval of statins would set precedence as the first approval of a drug made specifically for treating chronic diseases. This opens up the possibility for future prescriptions to be approved as over-the-counter drugs that will be accompanied with their unique benefits and inevitable risks.